Sex-related differences in Cushing's disease: a systematic review and meta-analysis - Basel F. Alqeeq; Mohammed Ayyad; Waseem J. Almadhoun; Mohammad Aboabdo; Mosheer S. Aldahdouh; Mohammed Al-Tawil; Ahmed M. Al-Ghazali (Annals of Saudi Medicine, 2024)
BACKGROUND AND OBJECTIVES: Cushing's disease is a rare endocrine disorder. This review aimed to examine sex-specific differences in Cushing's disease. DESIGN AND SETTINGS: A meta-analysis was performed on published articles discussing the gender impact of Cushing's disease. METHODS: A systematic search was conducted to identify studies from Medline, Embase, CENTRAL and Scopus. Nine studies enrolling 1047 patients diagnosed with Cushing's disease were included in this meta-analysis. RESULTS: Male patients presented at a younger age (MD [mean difference]=−5.43; 95% CI [−5.78, −5.08]; P<.00001) than females. Male patients had a significantly higher prevalence of osteoporosis (RR [risk ratio]=1.75; 95% CI [1.36, 225]; P<.0001) and hypokalemia (RR=1.66; 95% CI [1.27, 2.16]; P=.0002). In addition, males had significantly higher rates of negative magnetic resonance imaging (RR=1.53; 95% CI [1.18, 2.0]; P=.002). No sex difference was observed in the prevalence of diabetes (RR=0.92; 95% CI [0.70, 1.22]); P=.57) and dyslipidemia (RR=1.33; 95% CI [0.88, 2.0]; P=.17). CONCLUSION: Cushing's disease has a worse clinical presentation in males and more diagnostic difficulties compared to females.